Answer:
see explanation
Step-by-step explanation:
Using the trigonometric identity
sin²x + cos²x = 1 , then
sin²x = 1 - cos²x and cos²x = 1 - sin²x
Consider the left side
← expand numerator/denominator using FOIL
=
= ![\frac{1-(1-cos^2A)}{1-(1-sin^2A)}](https://tex.z-dn.net/?f=%5Cfrac%7B1-%281-cos%5E2A%29%7D%7B1-%281-sin%5E2A%29%7D)
= ![\frac{1-1+cos^2A}{1-1+sin^2A}](https://tex.z-dn.net/?f=%5Cfrac%7B1-1%2Bcos%5E2A%7D%7B1-1%2Bsin%5E2A%7D)
= ![\frac{cos^2A}{sin^2A}](https://tex.z-dn.net/?f=%5Cfrac%7Bcos%5E2A%7D%7Bsin%5E2A%7D)
= cot²A = right side , thus proven
Answer:
Step-by-step explanation:--0.9
108 mins✍ 48÷4=12 1 sprinkler takes 12 mins 48+48=96 = 8 sprinklers 1 more equals 12 so 96+12=108
Answer:
61.66
Step-by-step explanation:
1. Multiply
2. divide